Neo adult learners’ instructional learning model in higher learning education / Norraidah Abu Hasan ... [et al.] - Abu Hasan, Norraidah; Temyati, Zawawi; Kamarudin, Mohd Faizal; Susanto, Perengki (UiTM Press, 2024)
Open and Distance Learning (ODL) is important for lifelong learning, allowing adults to acquire new skills, update their knowledge, and stay relevant in an ever-evolving job market. A notable area for improvement is observed in the availability of a comprehensive framework to direct the formulation of Open and Distance Learning (ODL) environments that aptly cater to the requisites of adult learners. There needs to be a comprehensive framework to guide the design of ODL environments that meet the needs of adult learners and which is supported by adult learning theories, online knowledge construction, and technology acceptance. This paper examines the instructional designs intended to improve adult learner achievement and meet the self-empowerment needs of adult working students. The research will investigate the theories and perspectives on adult learning in higher education based on the existing literature. This research proposes the existence, relatedness, and growth (ERG) theory and the Heutagogy principle to capture the needs of adult learners from both positivist and subjectivist perspectives.